Mobile cloud computing: The-state-of-the-art, challenges, and future research - Abolfazli, S.; Sanaei, Z.; Sanaei, M.H.; Shojafar, M.; Gani, Abdullah (Willeys & Sons, 2015)
Mobile Cloud Computing (MCC) is the state-of-the-art distributed mobile computing technology that is recently gaining ground to augment computational capabilities of resource-constraint mobile devices using cloud-based resources. MCC employs Cloud-based Mobile Augmentation (CMA) approaches to efficiently execute resource-intensive components of mobile applications outside the device in a resource-rich cloud-based computing resource(s). However, employing CMA approaches is not a straightforward panacea and is encumbered by varied challenges, particularly long WAN latency. Researchers endeavored to mitigate the impacts of long WAN (Wide Area Network) latency by proposing varied architectures for MCC. In this chapter, we present comprehensive overview of MCC, present its definition, motivation, and taxonomy of MCC building blocks followed by brief comparison of cloud computing and MCC. Various MCC architectures are illustrated and scrutinized. Also several open challenges that require future research are presented.